Pozyskiwanie danych przestrzennych do rejestracji wydarzenia o charakterze masowym z wykorzystaniem bezzałogowego statku powietrznego - Smaczyński, Maciej (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
At present, Unmanned Aerial Vehicles show the world from a new perspective, formerly hardly accessible. The author made an attempt at examining the potential and the effectiveness of the innovative UAV (Unmanned Aerial Vehicle) technology for the purpose of taking a series of photographs during a mass event treated as a dynamic phenomenon. The aim of the study was to systematize the process of obtaining spatial data on mass events and to suggest the use of the appropriate research methods.
Keywords: UAV; BSP; GNSS; data acquisition; geomatics; mass events